Gender and support for creativity at work. (29th June 2020) - Taylor, Christa; Ivcevic, Zorana; Moeller, Julia; Brackett, Marc
Abstract : Although innovation is vital for the success of organizations, many may not be capitalizing on the creativity of all workers. Gender bias in attributions of creativity may lead to an imbalance in the extent to which organizations support the creativity of men and women. Because organizational support for creativity is positively associated with creative outcomes, this may undermine the creativity of women in the workplace. To determine if gender influences creative workplace behavior through support for creativity, conditional process models were used to analyze the survey responses and external employment data of workers ( N = 14, 590) across industries in the US. Our analyses demonstrate that men report greater support for creativity in the workplace than women, and greater support for workplace creativity leads to more frequent creative workplace behaviors. The proportion of women employed in an industry influences this relationship, such that differences between men and women become smaller as the proportion of women in an industry increases. However, the level of creativity required in an occupation does not influence the relationship between gender and creativity. The theoretical and practical implications of these results are discussed.